The Preliminary Prototype of Medium Dose Rate Brachytherapy Equipment - A. Satmoko; T. Harjanto; I.M. Putra; Kristiyanti Kristiyanti (PPIKSN-BATAN, 2013)
A preliminary prototype of a brachytherapy equipment has been constructed. The work started by developing conceptual design, followed by basic design and detailed design. In the conceptual design, design requirements are stated. In the basic design, technical specifications for main components are determined. In detailed design, general drawings are discussed. The prototype consists of three main systems: a mechanical system, an instrumentation system, and a safety system. The mechanical system assures the movement mechanism of the isotope source position beginning from the standby position until the applicators. It consists of three main modules: a position handling module, a container module, and a channel distribution module. The position handling module serves to move the isotope source position. As shielding, the second module is to store the source when the equipment is in standby position. The prototype provides 12 output channels. The channel selection is performed by the third module. The instrumentation system controls the movement of source position by handling motor operations. It consists of several modules. A microcontroller module serves as a control center whose task includes both controlling motors and communicating with computer. A motor module serves to handle motors. 10 sensors, including their signal conditionings, are introduced to read the environment conditions of the equipment. LEDs are used to display these conditions. In order to facilitate the operators’ duty, communication via RS232 is provided. The brachytherapy equipment can therefore be operated by using computer. Interface software is developed using C# language. To complete both mechanical and instrumentation systems performance, a safety system is developed to make sure that the safety for operator and patients from receiving excessive radiation. An interlock system is introduced to guard against abnormal conditions. In the worst case, a manual intervention by the operator is provided when all other means are failing to store the isotope source into the safe container. The tests showed good results. The prototype can send the isotope source to applicators. The isotope source can be positioned with an accuracy of ± 0.5 mm and with a speed of 550 mm/second. These characteristics meet the design criteria.Received: 16 January 2013; Revised: 26 August 2013; Accepted: 29 August 2013